PENGOLAHAN SAMPAH ORGANIK DAN ASPEK SANITASI - Wahyono, Sri (Jurnal Teknologi Lingkungan, 2001)
Organic waste is one of major problems that potentially degrade environmentalquality and public health so that it have to be treated proposionally. In therecent time, there are organic treatment technologies such as composting,incinerating, landfilling, etc. In this article, the author talks about organic wastetreatment and sanitation aspect of wastes.